Multilateral Debt Relief through the Eyes of Financial Markets - Raddatz, Claudio (MIT Press, 2015)
This paper conducts an event study of the impact of multilateral debt relief initiatives announcements on the stock prices of South African companies with subsidiaries in countries benefited by these initiatives. It shows that these prices increase significantly above those of other firms, especially around the launching of the Multilateral Debt Relief Initiative. These price increases are consistent with lower expected levels of future taxation in the benefited countries and provide evidence of the economic consequences of multilateral debt relief that is robust to reverse causality between economic performance and the decision to grant debt relief.